2012
DOI: 10.1186/1471-2407-12-377
|View full text |Cite
|
Sign up to set email alerts
|

The T-box transcription factor Brachyury regulates epithelial–mesenchymal transition in association with cancer stem-like cells in adenoid cystic carcinoma cells

Abstract: BackgroundThe high frequencies of recurrence and distant metastasis of adenoid cystic carcinoma (AdCC) emphasize the need to better understand the biological factors associated with these outcomes. To analyze the mechanisms of AdCC metastasis, we established the green fluorescence protein (GFP)-transfected subline ACCS-GFP from the AdCC parental cell line and the metastatic ACCS-M GFP line from an in vivo metastasis model.MethodsUsing these cell lines, we investigated the involvement of the epithelial–mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 57 publications
3
60
0
1
Order By: Relevance
“…These results are consistent with those of previous studies, which revealed that silencing brachyury expression inhibits tumor formation and metastasis in human adenoid cystic carcinoma cells (19,20). In addition, a previous study revealed that brachyury expression is associated with EMT and lymph node metastasis in OSCC patients (22).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with those of previous studies, which revealed that silencing brachyury expression inhibits tumor formation and metastasis in human adenoid cystic carcinoma cells (19,20). In addition, a previous study revealed that brachyury expression is associated with EMT and lymph node metastasis in OSCC patients (22).…”
Section: Discussionsupporting
confidence: 93%
“…However, the role of these genes in CSCs remains unclear. Recently, the T-box transcription factor brachyury, which is essential for mesoderm formation during early development (16,17), has been found to regulate the epithelial-mesenchymal transition (EMT) and CSC potential in human salivary carcinoma cells (18)(19)(20)(21). In addition, brachyury expression was found to correlate with lymph node metastasis in OSCC (22).…”
Section: Introductionmentioning
confidence: 99%
“…As the name implies, chordomas are thought to be of notochordal origin and one of the major roles of T is in the development of the notochord (Nibu et al, 2013). T has also been implicated in controlling EMT in some cancers such as adenoid cystic carcinoma and colorectal cancer (Sarkar et al, 2012;Shimoda et al, 2012).…”
Section: Cip1mentioning
confidence: 99%
“…Recently, Brachyury was associated with tumor aggressiveness in several tumor types (6)(7)(8)(9)(10)(11) and was found to be a significant predictor of poor prognosis in early colon cancer (8) and lung cancer (6). In vitro studies suggested that these associations are driven by EMT, accomplished by increased migratory and invasion capacity (12)(13)(14) and increased cancer stem cell features (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…In lung cancer cell lines, it was demonstrated that Brachyury blocks cell-cycle progression and, therefore, mediates tumor resistance (15). However, in adenoid cystic carcinoma cells, Brachyury promoted tumor growth and metastasis formation in vivo (11). Therefore, despite the described oncogenic role of Brachyury, some authors suggest that it can also act as a tumor suppressor gene (16).…”
Section: Introductionmentioning
confidence: 99%